Optimization algorithm for designing vertical alignments of highways / Zahriani Mastam - Mastam, Zahriani (Faculty of Civil Engineering, 2006)
Economic considerations are one of the most important design controls in highways project. Meanwhile, computerized highway optimization models can seek optimized horizontal and vertical alignments by minimizing aspects of total cost. Since the economic considerations become important part, cut and fill balance should be considered by minimizing earthworks which apparently may decrease the construction costs. This study describes the ability of dynamic programming for vertical alignment optimization of a highway. The results of this study proved that the dynamic algorithm can be applied in the optimization of vertical alignments road design.